What's Good on TV : Understanding Ethics Through Television. - Watson, Jamie Carlin (John Wiley & Sons, 2012)
What's Good on TV? Understanding Ethics Through Television presents an introduction to the basic theories and concepts of moral philosophy using concrete examples from classic and contemporary television shows. Utilizes clear examples from popular contemporary and classic television shows, such as The Office, Law and Order, Star Trek and Family Guy, to illustrate complex philosophical conceptsDesigned to be used as a stand-alone or supplementary introductory ethics textFeatures case studies, study questions, and suggested readingsEpisodes mentioned are from a wide variety of television shows, a.